LOAN CONDITIONALITIES OF INTERNATIONAL MONETARY FUND AND THE QUEST FOR POVERTY ALLEVIATION IN NIGERIA - ALOH, Johnson Ngwuta; IGBOKE, Shedrack C; EZE, Osmond Ikechukwu (Socialscientia: Journal of Social Sciences and Humanities, 2021)
There has been a growing debate on whether the policies and operations of the International Monetary Fund (IMF) have actually helped Africa to tackle two of the most important contemporary global goals – poverty and hunger. Many claim that the IMF has rather accentuated poverty in developing and underdeveloped climes than alleviate it. Against this backdrop, this paper investigates the role of IMF in alleviating poverty and hunger, and its implication to the attainment of the Sustainable Development Goals (SDGs) in Nigeria. The secondary source of data collection was used and Case Study method applied to overview the detailed and intensive analysis of the roles of IMF. Relying on dependency theory, our findings reveal that the IMF strategies have hitherto been counterproductive in its attempt at poverty reduction in Africa. The policies and conditionality of IMF lending do not show IMF’s genuine intention towards repositioning the country for significant poverty reduction and economic growth. Hence, Nigerian and African leaders are advised to look inward to solve the problems of poverty and hunger. The paper notes that with sincere and patriotic measures of diversification from the mono-economic base of Nigeria, economic growth will be achieved, hunger will be reduced, and sustainable development guaranteed.